Effects of Foxc1 and Oct4 genes regulating BMSCs transplantation on cardiomyocyte apoptosis after acute myocardial infarction in rats - ZHANG,Dongming (2022)
Abstract To investigate the effect of Foxc1 and Oct4 genes regulated by bone marrow mesenchymal stem cells (BMSCs) transplantation on cardiomyocyte apoptosis after acute myocardial infarction in rats. 180 healthy SD male rats were divided into 3 groups by random number table method, namely control group, acute myocardial infarction (AMI) group and BMSCs group. The rats were sacrificed 4 weeks after transplantation. The TUNEL method was used to detect the cardiomyocyte apoptosis index. The control group basically had no cardiomyocyte apoptosis, while the apoptosis indexes of AMI group (0.67 ± 0.14) was higher than that (0.31 ± 0.12) of BMSCs group (P < 0.05). The OD value of Foxc1 and Oct4 protein in BMSCs group was higher than those in AMI group (all P < 0.05). BMSCs transplantation can reduce cardiomyocyte apoptosis after AMI in rats. The mechanism may be related to the up-regulation of Oct4 and Foxc1 protein expression.